Aspects of the Postglacial Climate of Alberta: Calibration of the Pollen Record - Vance, Robert (Géographie physique et Quaternaire, 1986)
ABSTRACTThis reconstruction of the postglacial climate of Alberta is based on a review of pollen studies within the province and the application of calibration equations to a pollen record from central Alberta. Regional palynological studies indicate that the late glacial vegetation, dominated by non-arboreal taxa and, on occasion, Populus, was replaced by a Picea dominated assemblage between 12,000 and 10,000 BP. In central Alberta, increased herbaceous pollen representation suggests that grassland was established north of its current position in early to middle Holocene time. By 3500 BP, the grassland boundary had retreated southward. Little vegetational change is evident during the last 3500 years. Calibration equations, derived from modern pollen and climatic data in the western interior of Canada and applied to an 11,400 year pollen record, suggest growing season temperature was 1.5°C greater than at present while growing season precipitation was 50 mm below current values during the middle Holocene.